Analisis zat gizi dan biaya sisa makanan pada pasien dengan makanan biasa - Mihir Djamaluddin; Endy Paryanto Prawirohartono; Ira Paramastri (Jurnal Gizi Klinik Indonesia, 2005)
Background: The quality of food service in a hospital can be assessed from the inpatients’ nutritional status. Food waste is an indicator of food service among inpatients. Besides its therapeutic value, food has a significant economic value. The wasting cost in term of food waste affects the total availability of food costs.Objective: This study analyzes the nutrient quantity and the cost of food waste among inpatients with regular diet at Dr. Sardjito Hospital, Yogyakarta.Method: This was a cross sectional study. The subjects were inpatients aged 17 to 60 years old who got regular diet with length of stay was at least three days, and were willing to take part in this study (n=100). The amount of food waste was measured using the Comstock visual estimation. The cost of food waste was calculated as the proportion of food waste from cost per serving. The quantity of nutrients in food waste was calculated using the Food Processor 2 software. The data were analyzed using Chi-square test.Results: There was a difference of food waste according to gender. Rice waste was found more frequent among female (p<0,005). There was a difference of food waste according to ward class. There were more waste of meat and vegetables among inpatients in class II and the difference was significant (p<0,05). There were more waste of meat and vegetables among patients with length stay of 7 – 14 days and > 15 days (p<0,05). The vegetables and rice waste were more frequent among surgery and cancer inpatients (p<0,05). In average the nutritional value of food waste was 19,85% - 9,33% of a patient’s RDA, while the wasting cost per day was Rp 1265,08 or 10,79% of all food cost per day. The annual wasting cost of food waste was Rp 45.543.120 or 4,4% of the available budget of Rp 1.038.605.333,00.Conclusion: There were differences of food waste according to gender, ward class, length of stay, and kind of disease, especially rice, meat, and vegetables.